1999
DOI: 10.1109/23.819118
|View full text |Cite
|
Sign up to set email alerts
|

Predicting radiation response from process parameters: Verification of a physically based predictive model

Abstract: We evaluate the hole trapping rcsponsc of twcntytwo oxidcs subjected to twenty-two dikrcnt sets of processing parametcrs. Thc oxides were prepared in tbrec diffcrcnt €acilities, the Harris Semiconductor-Intersil Palm Bay facility, thc foriner Naval Research and Dcvclopinenl Laboratory (NRAD) 4" facility, aitd the new SPAWAR 6" fabrication facility in San Diego, Califoruia. In twenty of the tneiity-two cascs, oxidc hole trapping is almost coinplctcly determined by thc highest processing tcnipraturc aud is in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Recent experimental studies have shown that the oxygen vacancy E′ hole trap precursor has an activation energy of about 1.5 eV [18]- [22]. Several more recent theoretical studies have provided calculated values in good agreement with experiment [23], [24].…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…Recent experimental studies have shown that the oxygen vacancy E′ hole trap precursor has an activation energy of about 1.5 eV [18]- [22]. Several more recent theoretical studies have provided calculated values in good agreement with experiment [23], [24].…”
Section: Introductionsupporting
confidence: 54%
“…As mentioned previously, positively charged E′ centers dominate hole trapping in (thicker) oxides irradiated to moderate total dose levels. Recent experimental work [18]- [22] indicates that the oxygen vacancy E′ precursor has an enthalpy of creation of approximately 1.5 eV. Although these experimental results have been somewhat controversial on theoretical grounds [29], [30], at least two careful theoretical studies by independent groups have recently generated results in agreement with the (1.5 eV) experimental value [25].…”
Section: A the E′ Defect And Rilcmentioning
confidence: 58%
See 2 more Smart Citations
“…15 This assumption is in contrast to the vast majority of work on radiation effects 1 and is still to be verified. 16 Finally, within the context of the P b approach, and not necessarily in direct connection with the LITB, we would like to stress the importance of taking into account the concurrent running of interface-trap formation and passivation processes. 5 This fact has often been neglected in analysis of the postirradiation response of MOSFETs.…”
Section: ͓S0003-6951͑01͒02601-8͔mentioning
confidence: 99%